A Pilot Study of a Culturally Tailored Lifestyle Intervention for Chinese American Cancer Survivors. (21st December 2019) - Deng, Furjen; Chen, Danhong; Swartz, Maria C.; Sun, Helen
Although Asian Americans generally have the lowest cancer incidence rates and mortality rates, cancer is the leading cause of death among Asian Americans. The goal of this pilot study was to engage Chinese American cancer survivors (CACS) in systematic changes toward desired health behaviors through a healthy lifestyle intervention delivered by a community-based organization. The Reach out to ENhanceE Wellness (RENEW) program workbook was translated into Mandarin Chinese with additional physical activity (PA) and dietary information that are culturally appropriate (RENEW-C). Fifty-five Chinese cancer survivors were recruited from the greater Houston area to participate in this 50-week program and 50 of them completed both the baseline and postintervention surveys in 2013 and 2014, respectively. Paired sample t tests were used to assess changes in 5 groups of outcomes: (1) patient knowledge (measured by Health Education Impact Questionnaire [heiQ]), (2) dietary intake (Automated Self-Administered 24-Hour [ASA24] Dietary Assessment Tool), (3) PA (Community Healthy Activities Model Program for Seniors [CHAMPS]), (4) body mass index, and (5) quality of life (36-item Short-Form Survey [SF-36]). Compared with the baseline, participants reported significantly higher consumption of vegetables and higher frequency of PAs at the postintervention survey. They also showed improved mental health and lower limitation in doing their work or other activities due to physical health or emotional problems. Despite the small sample size, this pilot study demonstrated the effectiveness of using a community-based participatory approach in a healthy lifestyle intervention tailored for CACS.